Candidiasis as Secondary Infection in Post COVID-19: A New Problem? - Evelyn Nathania; Jahja Teguh Widjaja (Jurnal Respirasi, 2021)
Introduction: Severe Acute Respiratory Syndrome (SARS-CoV-2) can develop into post COVID-19 with one of its main attentions being secondary infection. Candidiasis as fungal pneumonia is one of secondary infection in post COVID-19. It is hard to diagnose and has high mortality. We present a case of candidiasis as fungal pneumonia in post COVID-19 patient.Case: A 47-year-old woman came to the emergency room with major complaints of dyspnoea and jaundice since her second day at home after being discharged from having COVID-19. She previously finished her COVID treatment and tested negative 2 times. She had severe sepsis and her sputum culture was positive for non-albicans Candida. She received anti-fungal treatment and her condition was getting better and her chest X-ray showed less infiltrates than before.Discussion: Fungal respiratory infections generate concern in the expanding population of immunosuppressed patients like COVID-19 patient. The mortality from COVID-19 associated candidiasis is high (19-40%) as one of fungal infection. Marked immune dysregulation in COVID-19 makes system immune becomes impaired, it also harms lung epithelium. In this patient, diagnosis and treatment were challenging.Conclusion: Post COVID-19 is a condition that should be given more attention, especially when it develops secondary infection. Candidiasis as fungal pneumonia is hard to diagnose and can quickly become severe sepsis and has high mortality. Health practitioners should recognize it as soon as possible and give the best treatment for the patient.